Studi Literatur: Pengaruh Kombinasi Kompres Hangat Terhadap Penurunan Skala Nyeri Atritis Gout Pada Lansia - Saharuddin; I Kadek Dwi Swarjana; Maria Yhunita; Nur, Akbar (Journal Kiara : Nursing and Midwifery, 2024)
Gout, also known as arthritis gout, is a degenerative disease that attacks the joints, and is most often found in the community, especially the elderly. Management of people with gout arthritis is focused on controlling pain. Pain can be minimized by providing non-pharmacological therapeutic measures and one of them is a warm compress. Purpose: to analyze / explain how the effect of warm water compresses on decreasing arthritis gout pain scale in the elderly. Methods: The method used in writing this literature review is by searching the internet from a database with high and medium quality criteria, namely Scopus, ProQuest, Pubmed, CINAHL and Scient Direct, but some journals also use a number of health links such as Curren nursing and others. , using keywords (influence, warm compress, arthritis gout). Results & Analysis: From 15 articles from 2015 to 2020, the inclusion criteria were obtained and analyzed, while the designs in this analysis were quasi-experimental (14 articles / research) and literature review (1 article / research), then there was 1 article. journals discussing warm water compresses, 7 journals discussing the combination of warm water with ginger decoction, and 1 journal each discussing the combination of warm water compresses (salt, cinnamon, lemongrass and moringa leaf soaks) on reducing the pain scale of arthritis gout in the elderly. Conclusions & Suggestions: the results of the analysis of this study indicate that there is an effect between compresses of warm water and warm water combined with (ginger, salt, cinnamon, lemongrass & moringa leaves) on reducing the scale of gouty arthritis pain in the elderly. So it is recommended that people with arthritis gout be able to apply this intervention so that the pain they feel can be reduced or lost.